Analysis of In Vitro Effects of Sex Steroids on Lymphocyte Responsiveness in Murrah Buffaloes (Bubalus bubalis) - Zahoor Ahmad Pampori; Sujata Pandita (Veterinary Medicine International)
Present study was carried out on forty four apparently healthy Murrah buffaloes of different age groups of both sexes to investigate the effects of sex steroids on cell mediated immunity in vitro. Estrogen inhibited proliferation in mitogen-stimulated lymphocytes from prepubertal but not post pubertal buffaloes of either sex. Estrogen at 100 pg/mL concentration stimulating the proliferation significantly (𝑃<0.05). in all groups and had higher stimulatory effect in lymphocytes from day 10 than day 0 of estrous cycle. Progesterone inhibited lymphocyte proliferation, and inhibition was directly related to the dose, in all groups of either sex. Testosterone did not inhibit proliferation at any dose level and did not show any consistent and lucid effects on lymphocyte proliferation. Present study revealed that buffalo lymphocytes produce appreciable amounts of NO in culture system after treatment with estradiol. Significantly high levels of NO in culture supernatant were found in prepubertal buffalo calves and least in post pubertal buffaloes, which had an inverse relation with lymphocyte proliferation in presence of estradiol. NO in culture supernatant was high at the lowest dose of progesterone which was proportional to the lymphocyte proliferation when treated with progesterone. No significant difference in NO culture supernatant was observed between different concentrations of testosterone treatment.